Tendencias, Rasgos y Calidad de La Información Económica de Los Diarios Chilenos - Vera Vera, Héctor (Re-presentaciones: Periodismo, comunicación y sociedad, 2008)
Is this a descriptive and investigative research that wants to set reliable quality indicators for jour- nalistic information, and which intends to have a comprehensive look of newsmedia trends, strategies and even even biases when releasing economic reports. The methodology works on two time spans of 45 days each and includes four relevant chilean newpapers of national coverage for analysis.